Sintomas depressivos e déficit cognitivo na população de 60 anos e mais em um município de médio porte do interior paulista - Gomes, José Evandro Marques; Ruiz, Tania [UNESP]; Corrente, José Eduardo [UNESP] (Sociedade Brasileira de Medicina de Familia e Comunidade (SBMFC), 2011)
Introduction: the world population is ageing, and Brazil follows this tendency, which requires the reorganization of society for care provision to older people. In such tendency, an increasing number of cases of depression and dementia is observed in addition to their association with other chronic-degenerative diseases. Objective: to estimate the prevalence of depression and cognitive-deficit symptoms in a population aged 60 years and older, residing in a middle-sized city in São Paulo state and to associate the population with other more prevalent chronic degenerative diseases. Methods: cross-sectional study on 364 older people using the following instruments: socio-demographic and morbidity, Mini Mental State Examination, Yesavage Scale, the Activities of Daily Living Scale, and the Instrumental Activities of Daily Living (IADL) Scale. The following were performed: statistical analyses of the instruments’ score frequencies; presentation and summarization of the variables; and the possible associations between depression/dementia by applying the χ2 test followed by fitting of a logistic regression model for ordinal data. Results: the suspected depression was found in 44% (160), and cognitive deficit was observed in 38.7% (141) aged. About 75% of the individuals with suspicion of depression or cognitive deficit had at least another chronic pathology. It was possible to establish statistically significant associations between suspected depression and IADL (p<0.0001; OR=7.59; CI=3.361-7.139) and cognitive deficit and IADL (p=0.0007; OR=3.967; CI=1.788-8.799). No associations were found between age, marital status, schooling, placement in the work market, retirement or income. Conclusion: male and female older individuals are vulnerable to diseases, such as depression and dementia. On the other hand, depression symptoms and cognitive deficit were associated with the score of compromised older individuals, according to IADL.

Introducción: la población mundial está envejeciendo y Brasil sigue esta tendencia, que requiere una reorganización de la sociedad para el cuidado de los ancianos. Acepta-se que este número creciente de casos de la depresión y la demencia están asociados con otras enfermedades crónicas. Objetivo: estimar la prevalencia de los síntomas depresivos y deterioros cognitivos en una población de 60 años y más de edad, residente en una ciudad de tamaño medio en el Estado de São Paulo y su asociación con las enfermedades crónicas más frecuentes. Métodos: estudio transversal con 364 pacientes, utilizando los siguientes instrumentos: variables socio-demográficas y de morbilidad, el Mini Examen del Estado Mental, Yesavage Escala y Escala de Actividades de la Vida y Actividades Instrumentales de la Vida Diaria. Se realizaron: análisis estadísticos de frecuencias de las puntuaciones de los instrumentos; la presentación de los resúmenes de las variables y se estudiaran las posibles asociaciones entre la depresión y la demencia mediante la aplicación de la prueba de χ2 seguido por el ajuste de un modelo de regresión logística para datos ordinales. Resultados: la depresión fue encontrada en el 44% (160) y el deterioro cognitivo fue identificado en 38,7% (141) de las personas mayores. En aproximadamente el 75% de los pacientes ancianos con depresión, también se sospechó de deterioro cognitivo en los pacientes que tuvieron al menos una enfermedad más crónica. Fue posible establecer asociaciones estadísticamente significativas entre: sospecha de depresión y AIVD (p<0,0001, OR=7.59, IC=3,361- 7,139) y déficit cognitivo y AIVD (p=0,0007; OR=3,967; IC=1,788-8,799). No se encontró asociación entre sospecha de depresión y déficit cognitivo con la edad, el estado civil, la educación, la entrada en el mercado de trabajo, los ingresos o la jubilación. Conclusión: los adultos mayores de ambos los sexos son vulnerables a enfermedades como la depresión y la demencia. Por otra parte, los síntomas depresivos y el déficit cognitivo fueron asociados a la puntuación de los ancianos comprometidos, segundo el AIVD.

Introdução: a população mundial está envelhecendo e o Brasil segue essa tendência, o que demanda uma reorganização da sociedade para o cuidado desses idosos. Observa-se, nesta tendência, um aumento do número de casos de depressão e demência, além da vinculação destas com outras doenças crônico-degenerativas. Objetivo: estimar a prevalência dos sintomas depressivos e déficits cognitivos em uma população de 60 anos e mais, moradora de um município de médio porte do interior do estado de São Paulo, e sua associação com outras doenças crônico-degenerativas mais prevalentes. Métodos: estudo transversal, com 364 idosos, utilizando: instrumentos sociodemográficos e de morbidade; o Mini Exame do Estado Mental (MEEM), a Escala de Yesavage, a Escala de Atividades de Vida Diária e a Escala de Atividades Instrumentais de Vida Diária (AIVD). Foram realizadas: análises estatísticas de frequências dos escores dos instrumentos; apresentação da sumarização das variáveis e as possíveis associações entre depressão/demência, aplicando-se o teste do χ2 seguido do ajuste de um modelo de regressão logística para dados ordinais. Resultados: a suspeita de depressão foi encontrada em 44% (160) e o déficit cognitivo foi identificado em 38,7% (141) dos idosos. Aproximadamente 75% dos idosos, com suspeita de depressão ou déficit cognitivo, eram portadores de pelo menos mais uma patologia crônica. Foi possível estabelecer associações estatisticamente significativas entre: suspeita de depressão e AIVD (p<0,0001; OR=7,59; IC=3,361-7,139) e déficit cognitivo e AIVD (p=0,0007; OR=3,967; IC=1,788-8,799). Não foram encontradas associações entre idade, situação conjugal, escolaridade, inserção no mercado de trabalho, aposentadoria ou renda. Conclusão: idosos de ambos os sexos estão vulneráveis a doenças como depressão e demência. Por outro lado, sintomas depressivos e déficit cognitivo foram associados ao escore dos idosos comprometidos, segundo as AIVD.
Depression symptoms and cognitive-deficit in a population aged 60 years and older in a medium-sized city in São Paulo state, Brazil
Síntomas depresivos y de déficit cognitivo en la población de 60 años y más en una ciudad de tamaño medio en el estado de São Paulo, en Brasil
Keywords: Health of the elderly; Depression; Mental disorders; Neurobehavioral manifestations; Geriatric assessment; Saúde do idoso; Depressão; Transtornos mentais; Manifestações neurocomportamentais; Avaliação geriátrica